Probing spin-spin coupling constants in 2-halocyclohexanones and 2-halocyclohexanothiones: the role of the perlin, solvent and stereoelectronic effects - Rezende, Fátima Maria Pereira de (2019)
Long-range coupling studies 4JH2,H6were performed for 2-halo-cyclohexanones and cyclohexanthiones substituted by (F, Cl and Br). NBO calculations and coupling constants were performed with the objective of evaluating the effect of the halogen and electron acceptor character of the *orbital on the said coupling constants. The results pointed to hyperconjugative interactionsC2H2→*C1=YandC6H6→*C1=Y (Y = O and S) for the equatorial forms of the compounds replaced by F, Cl and Br, which probably contribute to the mechanism of transmission of4JH2,H6. The interactionsC2H2→*C1=YandC6H6→*C1=Y are higher for thiocarbonyl compounds, but the values of 4JH2,H6are higher for the carbonyl compounds. This is because the term Fermi (FC), which is influenced by the character of bonding lengths between the atoms involved in the coupling pathway, for thiocarbonyl compounds undergoes a larger decay than for the ketones, reducing the value of4JH2,H6. The implied solvent effect (DMSO and water) at the values of the coupling constant was insignificant when compared to the gas phase. On the other hand, the effect of the explicit solvent on 4JH2,H6was more sensitive for thiocarbonyl compounds than for cyclohexanones. The different halogens do not affect the magnitude of4JH2,H6. Also performed were Perlin effect studies for 2-halo-cyclohexanones and cyclohexanthiones substituted by (F, Cl and Br). The Perlin effect is an NMR phenomenon observed in six-membered rings and is referred to as 1JC-Hax <1JC-Heq. In this work, the influence of halogens (F, Cl and Br) at position 2 in cyclohexanones and cyclohexanthiones is theoretically evaluated in the C2 - H2 coupling constants of a bond, i.e. in the Perlin effect. An important hyperconjugative interaction (C=Y→*C-H, Y = O e S) operating in the systems studied seems to play a significant role for the observed behavior of 1JC-Hax <1JC-Heq. In addition, the contribution of Lewis (1JLewis) dominates the Fermi Contact term (1JFC), which plays the leading role for the C-H coupling constant of a general bond. In comparison with the gas phase, this behavior was considered insensitive to implicit solvents (DMSO and water).